Sensitivity to reward and punishment: Associations with diet, alcohol consumption, and smoking. (January 2015) - Tapper, Katy; Baker, Louise; Jiga-Boy, Gabriela; Haddock, Geoffrey; Maio, Gregory R.
Highlights: Links between reward/punishment sensitivity and health behaviours were examined. Higher overall reward sensitivity predicted higher fat intake. The Fun Seeking component of reward sensitivity predicted more smoking and higher alcohol intake. Higher punishment sensitivity predicted lower alcohol intake. Higher punishment sensitivity also predicted higher sugar intake. Abstract: This study examined whether sensitivity to reward predicts a range of potentially health-damaging behaviours. Secondary objectives were to explore the relationship between these behaviours and sensitivity to punishment. Sensitivity to reward and punishment were assessed among 184 individuals using questionnaire measures of Behavioural Approach System (BAS) and Behavioural Inhibition System (BIS) sensitivity. Participants also completed a food frequency questionnaire and measures of alcohol consumption and smoking. Higher BAS sensitivity predicted higher fat intake, higher alcohol consumption, greater likelihood of binge drinking, greater likelihood of being a smoker and, amongst smokers, smoking frequency. Higher BIS sensitivity predicted lower alcohol consumption but higher sugar intake. Thus, sensitivity to reward appears to be a risk factor for lifestyle behaviours that contribute to poor health. Whilst BIS sensitivity seems to offer some protection with respect to alcohol intake, the results suggest that this does not extend to health-related behaviours, in which the negative consequences may be less immediate. Instead, BIS sensitivity predicted higher sugar intake. This is consistent with the view that BIS sensitivity leads to higher anxiety, which individuals may attempt to regulate by indulging in sugary foods.